2019
DOI: 10.1108/joe-01-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Professionals’ involvement of relatives – only good intentions?

Abstract: Purpose The purpose of this paper is to explore how, and under what conditions, professionals involve relatives in clinical practice. Design/methodology/approach Two cases were constructed from two studies in Denmark, theoretically inspired by Bourdieu’s concepts of doxa and position and analyzed with focus on the involvement of relatives from the perspective of professionals. Findings Support to relatives in practice is rarely included in the way that treatment and care are organized in healthcare. Profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 49 publications
2
29
0
11
Order By: Relevance
“…Nurses are socialised into the role of assistants to doctors, and the medical logic unconsciously rules their practical sense in specialised palliative homecare. It is important to be aware of how, historically, nursing is embedded in the medical field, which has significance for the context in which nursing is carried out in palliative homecare and the conditions under which nurses perform their jobs (Glasdam 2007;Carlhed 2007;Glasdam and Oute 2018). According to Bourdieu (1996b), an acquired habitus maintains an order that classifies people and knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses are socialised into the role of assistants to doctors, and the medical logic unconsciously rules their practical sense in specialised palliative homecare. It is important to be aware of how, historically, nursing is embedded in the medical field, which has significance for the context in which nursing is carried out in palliative homecare and the conditions under which nurses perform their jobs (Glasdam 2007;Carlhed 2007;Glasdam and Oute 2018). According to Bourdieu (1996b), an acquired habitus maintains an order that classifies people and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we regarded specialised palliative homecare as a space in the field of medicine. Many studies showed how the logic of medicine, including palliative care, is based on an individualistic, bio-medical rationality, in which the diagnosis is foundational for making valid interpretations of the patient's somatic condition and accurate decisions about his/her treatment (Glasdam 2007;Mol 2008;Engström 2012;Højskov and Glasdam 2014;Glasdam and Oute 2018). It has also been shown that the logic of medicine formed an organising policy for clinical practice.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The nurses' articulations, priorities and views on sexual health are governed by the medical logic that dominates the oncological clinic specifically (Glasdam, 2007;Karidar et al, 2016) and health care in general (Ellegaard & Dybbroe, 2015;Fox, Antony, Foley, O'Sullivan, & Timmons, 2018;Glasdam & Oute, 2018). Sabatino et al (2014) show how the dominance of medical logic reflects an environment where the medical discourse is at the top of the healthcare hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…This means that personal chemistry, as a guide for attention on sexual health and professional help, has an embedded risk of including patients living and thinking in the same way as nurses, the middle class and excluding patients from other social classes (Glasdam, 2007;Glasdam, Timm, & Vittrup, 2010). Many studies show how nurses have a gatekeeper function, for example, in relation to involving children in their parent's illness situation (Karidar et al, 2016), involving relatives in the medical clinic (Glasdam, 2007;Glasdam & Oute, 2018), shaping patients' experiences of health care, and producing opportunities to enable or constrain their choices (Collyer, Willis, & Lewis, 2017). By using personality and chemistry as indicators for professional attention and help regarding sexual health, nurses shape a patient as a picture of the potential self.…”
Section: Discussionmentioning
confidence: 99%